A Subset of Malignant Mesotheliomas in Young Adults Are Associated With Recurrent EWSR1/FUS-ATF1 Fusions. (July 2017) - Desmeules, Patrice; Joubert, Philippe; Zhang, Lei; Al-Ahmadie, Hikmat A.; Fletcher, Christopher D.; Vakiani, Efsevia; Delair, Deborah F.; Rekhtman, Natasha; Ladanyi, Marc; Travis, William D.; Antonescu, Cristina R.
Abstract : Malignant mesothelioma (MM) is a rare, aggressive tumor often associated with asbestos exposure and characterized by complex genetic abnormalities, including deletions of chromosome 22. A gene fusion involving EWSR1 and YY1 gene on 14q32 has been reported in 2 patients over the age of 60 with peritoneal MM. However, the incidence of EWSR1 rearrangements in MM and the spectrum of its fusion partners remain unknown. We recently encountered 2 MM cases with EWSR1-ATF1 fusions and sought to investigate the prevalence and clinicopathologic features associated with this abnormality. As both index cases occurred as intra-abdominal tumors in young adults, we searched our files for pleural and peritoneal MM occurring in adults younger than age of 40. All cases were tested by fluorescence in situ hybridization using custom bacterial artificial chromosomes probes for EWSR1, FUS, and ATF1 genes. When available, immunohistochemistry for BAP1 was performed. A total of 25 MM from patients aged 40 or less were screened, either from peritoneum (n=13) or pleura (n=12), with a median age of 31 (range: 7 to 40 y). Two additional ATF1 -rearranged tumors were identified at pleural and peritoneal sites with EWSR1 and FUS as fusion partners, respectively, for a total of 4 cases (16%, 4/25). The fusion-positive cases displayed classic epithelioid morphology, immunoreactivity for cytokeratins and WT1, and negativity for S100. BAP1 expression was retained in the 3 fusion-positive cases with available material, and in 80% (12/15) of the fusion-negative cases. Our results expand the spectrum of tumor types harboring EWSR1/FUS-ATF1 gene fusions to include a subgroup of conventional epithelioid MM. Other features of this unique MM subset include young age at presentation, lack of asbestos exposure and retained BAP1 expression. Abstract : Supplemental Digital Content is available in the text.